(untitled) (Window of Public Health Journal, 2025)
Cigarettes are risky objects that are harmful to health, although they can provide a sense of relaxation and psychological effects. The shape is a cylinder with a length of between 70 and 120 mm and a diameter of approximately 10 mm, containing chopped tobacco leaves. This study aims to determine the relationship between the level of knowledge, attitudes, and actions towards the smoking habits of traders in Butung Market, Makassar. The findings underscore the importance of awareness, encouraging traders and policymakers to recognize their role in health promotion. Data analysis was carried out using a bivariate test approach using the chi-square correlation test. The number of samples in this study was 89 respondents. The instrument used in this study was a questionnaire. From the results of the study, it was concluded that there was a significant relationship between the level of knowledge of traders and smoking habits with a value of p = 0.000 (<0.05), there was a relationship between attitudes and smoking habits with a value of p = 0.000 (<0.05), there was a relationship between traders’ actions and smoking habits with a value of p = 0.000 (<0.05) in Butung Market, Makassar. The suggestion that researchers can provide based on the results of this study is that the team from Butung Market management should provide regular counseling about cigarettes to traders, so that traders are more aware of cigarettes and the impacts they cause.